Renal Denervation in Patients With Moderate to Severe Chronic Kidney Disease - Schlaich, Markus P.; Mahfoud, Felix; Böhm, Michael; Narkiewicz, Krzysztof; Ruilope, Luis; Williams, Bryan; Mancia, Giuseppe; Sharif, Faisal; Ribichini, Flavio; Lung, Te Hsin; Shetty, Sharad; Schmieder, Roland (Hypertension, 2025)
BACKGROUND: Uncontrolled hypertension is common in patients with chronic kidney disease (CKD), putting these patients at high risk for adverse cardiovascular events. Radiofrequency renal denervation (RDN) lowers blood pressure (BP) in patients with hypertension. The Global SYMPLICITY Registry DEFINE enrolled over 3500 patients with uncontrolled hypertension worldwide, including patients with moderate-to-severe CKD. METHODS: Patients were categorized by their baseline estimated glomerular filtration rate (estimated glomerular filtration rate [eGFR], mL/min per 1.73 m2): eGFR ≥60 (no-CKD, n=2539), eGFR ≥45 to <60 (stage 3a, n=496), eGFR ≥30 to <45 (stage 3b, n=256). BP changes from baseline through 3 years were compared between groups. One-year data for 74 CKD stage 4 patients were also assessed. Safety events and eGFR were reported at all time points. RESULTS: Average baseline office systolic BP was similar across the 3 comparator groups (range: 162.8±26.4-164.7±24.8 mm Hg). At 3 years, office systolic BP reductions from baseline were -17.2±28.1 mm Hg, -12.1±30.3 mm Hg, and -13.0±27.3 mm Hg in the no-CKD, CKD 3a, and CKD 3b groups, respectively (all P<0.0001). A mild decline in eGFR through 1 year occurred in the no-CKD group but not in any CKD group. Three-year mortality was 4.3%, 7.0%, and 15.2% in no-CKD, CKD 3a, and CKD 3b groups, respectively. Adverse renal events were rare (<1.0%) across all 3 groups. Antihypertensive medication burden remained high in the no-CKD and CKD 3a groups but declined over 3 years in the CKD 3b group (P=0.007). CONCLUSIONS: In patients with uncontrolled hypertension and moderate-to-severe CKD, radiofrequency RDN results in clinically meaningful and durable BP reduction without renal or vascular safety concerns. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT01534299.
CRIS-Team Scopus Importer:2025-11-28
Keywords: blood pressure; denervation; hypertension; kidney; sympathetic nerves